Attacking Africa's Poverty : Experience from the Ground. - Fox, M. Louise; Liebenthal, Robert (World Bank e-Library., 2006)
By all measures, poverty in Africa as a whole has increased and deepened. But in fact, Africa contains a number of undocumented success stories of poverty reduction. This book presents case studies of thirteen of these success stories, giving grounds for some real hope, and providing useful learning for all? policymakers, governments, businesses, service providers, NGOs, and donors.